Management of Professional Training and Development Programs for Arabic Language Teachers for Non-Native Speakers - M Sholih Salimul Uqba; Achmad Syaifuddin Zuhri; Dendy Hermawan; Nuril Mufidah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to analyze the management of training and development programs for Arabic language teachers in Madrasah Aliyah Mamba’ul Ulum, Bungah, Gresik. This research was descriptive qualitative and collected through observation and interview. The data was analyzed through the three steps namely data reduction, data presentation, and conclusion drawing. The findings showed that only few of Arabic language teachers have appropriate academic qualifications, with details that there were 3 Arabic language teachers, but there was only one teacher who had a bachelor’s degree in Arabic Language Education, while other teachers had a bachelor’s degree in Islamic Religious Education and Islamic Boarding School graduates. Then, the professional development program for Arabic teachers was held in the form of workshops and seminars related to learning twice in the last three years. However, the material presented only focuses on teaching materials according to the national curriculum, without any programs or activities to improve the ability of teachers to choose active, effective, and efficient learning methods. In conclusion, Arabic teacher qualifications are poorly managed at Madrasah Aliyah Mamba’ul Ulum, Bungah, Gresik, regardless of the fields’ quality of teachers or suitability.